Technological interventions: a pathway to combatting judicial corruption - Syauket, Amalia; Wijanarko, Dwi Seno; Lestari, Tyastuti Sri; Ismaniah, Ismaniah (Department of Government Studies, Universitas Muhammadiyah Makassar, 2024)
This study aims to find out whether corruption in the court can be prevented with Information Technology (IT). This research uses a qualitative descriptive approach where the main data source can be processed from relevant and current literature material with the theme of this article as secondary data. Information technology is the most influential factor in changing the world today. The administration of justice is an activity that includes the provision of information, communication, and production of new information. There is no denying that information technology will affect the way justice administration works. Corruption that often occurs in courts (judicial commissions) is in the form of petty corruption, namely administrative or bureaucratic corruption with a power approach, namely the exclusive power of decision makers. The results showed that optimal use of IT can support efforts to eradicate corruption in the court by using E-Court, paperless court, E-Filing, E-Skum, E-Payment, E-Summons applications. These various applications can prevent judicial corruption due to the application of transparency principles, efficiency principles such as cost savings, reduction of illegal levies, ease of information transfer, reduction of case broker practices, reduction of opportunities for corruption due to potential conflicts of interest and face. -face-to-face, reducing gratification and bribery which are the main requirements of smart governance so that efforts to eradicate judicial corruption can be effective.